2007
DOI: 10.1016/j.pain.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cortical dysfunction in patients with temporomandibular disorders in association with jaw movement observation

Abstract: Temporomandibular disorders (TMD) represent a group of chronic painful conditions in the masticatory musculature and temporomandibular joint. To examine possible changes in cortical machinery in TMD patients, we compared neuromagnetic signals evoked by cortical neurons between healthy subjects and TMD patients while they were carefully observing the video frames of jaw-opening movements performed by another person. During the movement observation task in the healthy subjects, we found cortical activation in t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
2
21
2
Order By: Relevance
“…This is supported by an MEG brain imaging study finding a left hemispheric specialization of mirror neurons regarding movements of the temporomandibular joint. Healthy subjects showed left lateralized activation in the inferior parietal cortex, the anterior part of the inferior-lateral precentral gyrus and the occipitotemporal region during movement observation of symmetrical jaw-opening [Shibukawa et al, 2007]. The same group found no hemispheric specialization in jaw movement preparation [Shibukawa et al, 2004].…”
Section: Discussionmentioning
confidence: 87%
“…This is supported by an MEG brain imaging study finding a left hemispheric specialization of mirror neurons regarding movements of the temporomandibular joint. Healthy subjects showed left lateralized activation in the inferior parietal cortex, the anterior part of the inferior-lateral precentral gyrus and the occipitotemporal region during movement observation of symmetrical jaw-opening [Shibukawa et al, 2007]. The same group found no hemispheric specialization in jaw movement preparation [Shibukawa et al, 2004].…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have suggested that passive viewing of BM (particularly of goal-directed hand action and of mouth movement [23]) alone could activate various brain regions [24][26] that are thought to have a role in the human MNS. In agreement with these earlier studies, four to eight ECDs were estimated in both hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…Equivalent current dipoles were determined by least-squares search, based on signals from 20-30 channels over the response area. Only dipoles attaining a more than 90% goodness-of-fit were accepted for further analysis, where the entire time period and all channels were taken into account in computations of the parameters of a time-varying dipole model (Shibukawa et al, , 2006. In this model, the strength of the dipoles was allowed to change as a function of time.…”
Section: Introductionmentioning
confidence: 99%